Serological prevalence of FeLV and FIV in cats in Peninsular Malaysia. - Sapian, Nurul Ashikin; Arshad, Siti Suri; Dhaliwal, Gurmeet Kaur; Bande, Faruku (2011)
Feline Leukemia (Fel.V) and Feline Immunodeficiency Virus (FIV) are the two feline retroviruses that were studied in 65 client-owned cats from eight veterinary centres in selected areas throughout Peninsular Malaysia during a 4-week period. Blood samples were collected for serological tests using SensPERT®FeLV Ag/FIV Ab test kits. Five of 65 cats (7.69%) tested positive for the FeLV antigen and 10 cats (21.54%) tested positive for FIV antibodies. Only one cat had a dual infection. Chi square analysis revealed a significant association (P<0.05) between the health status and lifestyle of the cat and FeLV-positive status. FeLV infections were more likely to occur in a pedigree, adult male cat while FIV was more likely to infect the adult, intact cat that is aggressive towards other cats.